Prevalence of Chlamydia trachomatis at Pregnants Admitted in the Public Health Maternity - Carvalho, Newton Sergio de; Pegonaro, Mariana G.; Takimura, Marcos; Oliveira Jr, Fernando Cesar (Brazilian Journal of Sexually Transmitted Diseases, 2010)
Introduction: Chlamydia trachomatis (CT) is one of the main agents related with adverse outcomes in pregnant women in Brazil. Is involved in premature labor, premature rupture of membranes, ectopic pregnancy and recurrent abortion, as well as conjunctivitis and pneumonia in the newborn. The prevalence of infection varies according to diagnosis method and target population. Objective: the goal from this study was to estimate the prevalence of CT infection in young pregnant women, between 18 and 24 years, admitted in the emergency room of the Maternity Victor Ferreira do Amaral the Obstetric Low Risk Sector from Gynecology and Obstetrics Department; The characterization from risk behaviors by assessing epidemiological data to identify the determinants conditions for CT infection in this population was evaluated. Methods: this study is part of a multicenter study, nationwide, cross-sectional data collection was performed during the period between July 2009 and January 2010. Urine samples were collected during hospitalization and analyzed by PCR for identification of CT. In addition, a questionnaire was administered covering socio-demographic, obstetric and gynecological risk behavior for sexually transmitted diseases. Results: the results obtained from 65 urine samples collected in this interin analysis showed four subjects positives for CT, indicating a prevalence of 6.15%. Risk factors for STDs, such as the presence of early sexual activity and low age from the pregnant was positively associated with the infection. Conclusion: the prevalence of infection was 6.15%, lower than those obtained in other populations of pregnant women who used methods for collecting endocervical. The risk factors found relating with CT were absence of sexual relationship with the same partner, younger age from the pregnant and presence of association with other STDs. The CT screening in pregnant women is justifiable in addition with an evaluation from the risk factors.